2003
DOI: 10.1097/01.blo.0000068360.47147.30
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Cobb Angle in Idiopathic Adolescent Scoliosis

Abstract: We did a prospective study of 291 children and adolescents with idiopathic scoliosis to identify possible correlations between clinical (scoliometer value, age, height) and radiographic (Cobb angle, Nash-Moe rotation, Risser iliac apophysis classification) parameters to predict the curve angle. There was a statistically significant correlation between thoracic, thoracolumbar, and lumbar scoliometer values and the thoracic, thoracolumbar, and lumbar Cobb angles, respectively (Pearson's r-0.685, 0.572, and 0.677… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
2
37
2
4
Order By: Relevance
“…These methods emerged as an alternative to the radiographic evaluation method as it reduces exposure of patients who have scoliosis to excessive radiation, it is easier to evaluate in the clinic and it has a reduced cost, when compared to radiographic examination. Examples of these non-radiographic methods are the Moiré photograph [4][5][6] , the Quantec System 7 , the electric goniometer 8 and the scoliometer 2,3,[9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…These methods emerged as an alternative to the radiographic evaluation method as it reduces exposure of patients who have scoliosis to excessive radiation, it is easier to evaluate in the clinic and it has a reduced cost, when compared to radiographic examination. Examples of these non-radiographic methods are the Moiré photograph [4][5][6] , the Quantec System 7 , the electric goniometer 8 and the scoliometer 2,3,[9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there has been no consensus regarding the correlation of these values. Mubarak et al 13 , Amendt et al 9 and Pearsall et al , Sapkas et al 11 and Griffet et al 16 found a high correlation between the axial trunk rotation (ATR) values and the Cobb angles.…”
Section: Introductionmentioning
confidence: 99%
“…These patients' excessive exposure to radiation has been associated with an increased risk of developing breast cancer up to 5.4% 4 . Several non-invasive and radiation-free methods have been proposed to measure scoliotic deformities [5][6][7][8] , including the scoliometer [9][10][11] . The scoliometer is an inclinometer that measures the asymmetries between the sides of the trunk in axial rotation degrees.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule of thumb for estimating the Cobb angle, the values measured with the scoliometer can be multiplied by 3 for the thoracic spine and by 2 for the lumbar spine. The large individual spread must, however, be respected [18]. In ''Conclusion'', we usually indicate an X-ray when measuring an angle of trunk rotation C5°.…”
Section: Physical Examinationmentioning
confidence: 99%